Oxidative stress in the climacteric woman - Pacheco Romero, José (2015)
The climacteric is the time of the woman when she spends playing status to non-breeding, the latest one occurring menopause menstruation normally during that period, which occurs around age 51. Is a step immersed in the aging process.